(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Dengue fever is a major public health problem in tropical countries and is associated with significant morbidity and mortality due to its unpredictable clinical course. Early identification of patients at risk of developing severe dengue remains a clinical challenge. Electrolyte disturbances, particularly hypocalcemia, have been increasingly recognized in dengue infection. Ionized calcium represents the physiologically active fraction of serum calcium and may better reflect disease severity than total serum calcium. Aim: To assess the association between serum ionized calcium levels and the severity of dengue fever. Objectives: To estimate ionized calcium levels in patients with dengue fever, to classify dengue severity according to WHO 2009 criteria, and to evaluate the association between ionized calcium levels and clinical as well as laboratory indicators of disease severity.